Xanthogranulomatous appendicitis; a diagnostic challenge: Clinical Case: Apendicitis xantogranulomatosa; un desafío diagnóstico: Caso Clínico - Hernández-Morán, Alan A. (2022)
Introduction: Xanthogranulomatous inflammation is a chronic inflammatory process, rarely located in the appendix. A case of xanthogranulomatous appendicitis is presented. Clinical case. A 77-year-old male presents with intermittent pain in the right hemiabdomen and hyperthermia of one month's evolution. Physical examination showed a tumor in the iliac fossa and right abdomen. He underwent surgery for a probable incarcerated right inguinal hernia, acute perforated appendicitis was found, with inflammation and adhesions, purulent fluid in the right hemiabdomen and abdominal wall dissection. The histopathological result was xanthogranulomatous appendicitis. The evolution of the patient was favorable. Conclusion. Xanthogranulomatous appendicitis simulates a typical picture of acute appendicitis. Histopathologically, pathologies such as Crohn's disease, malacoplakia and tuberculous appendicitis were ruled out.